PEMANFAATAN DAN PELESTARIAN RAWA JOMBOR GUNA MENDUKUNG PENGHIDUPAN BERKELANJUTAN MASYARAKAT DESA KRAKITAN, KECAMATAN BAYAT, KABUPATEN KLATEN - , HARITS NOORDIN, Prof. Dr. Muhammad Baiquni, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Utilization of The Jombor Swamp which not balanced by conservation efforts have resulted in varieties of environmental problems, resulting loss and threaten community sustainable livelihoods. This research was conducted with the focus on: 1) community sustainable livelihoods associated with the utilization of swamp, 2) perceptions and participation, and 3) policy direction on the swamp utilization and conservation. The research methods used census with 85 respondents, in-depth interviews with government agencies related to the Jombor Swamp management, and observation methods. Methods of data analysis in this study are: the application of sustainable livelihoods framework, chi-square statistical analysis and descriptive analysis. The studi shown that: 1) community was implemented sustainable livelihoods framework, by doing a livelihood strategies in order to deal with various kind of vulnerabilities that affect their livelihood, such as catastrophe, rising prices of fish feed, declining visitors, and dry season, 2) most of the community who use the swamp as a source of livelihood (96.5%) have a high perception in conservation of the swamp, and 61.2% community have a high participation in conservation of swamp, how ever 84.7% community still have a desire to expand its business area to increase their profit, 3) restructuring and restriction of Jombor Swamp utilization for fish farming on floating net and culinary shop become the main objective of the swamp utilization and conservation policies.